2020
DOI: 10.3390/info11100478
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of eWOM, Trust Inclination, and Information Adoption on Purchase Intentions in an Accelerated Digital Marketing Context

Abstract: The study focuses on the canvas of online information transmission that has expanded exponentially. Especially due to social media networks, consumers have been exposed to significant amounts of disinformation, misinformation and actual information. Electronic word-of-mouth (eWOM) on social media networks has been facilitating swift information spread. Henceforth, it has become increasingly problematic for consumers to adopt authentic information and differentiate between marketers-generated content and user-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 35 publications
4
55
0
4
Order By: Relevance
“…As was described in Section 3.1, obtaining satisfaction positively affects trust, especially in virtual contexts [7], although C2C-platform trust is more complex than other ecommerce methods [80]. In this respect, the prior literature showed that, in a general way, the use of eWOM supports the growth of sales [19]. At the same time, these findings allow to affirm that consumers consider the trust dimension to make decisions related to purchases [14], such as satisfaction.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…As was described in Section 3.1, obtaining satisfaction positively affects trust, especially in virtual contexts [7], although C2C-platform trust is more complex than other ecommerce methods [80]. In this respect, the prior literature showed that, in a general way, the use of eWOM supports the growth of sales [19]. At the same time, these findings allow to affirm that consumers consider the trust dimension to make decisions related to purchases [14], such as satisfaction.…”
mentioning
confidence: 57%
“…In this manner, C2C ecommerce enables tools to facilitate consumers' opinions to reduce purchasing uncertainties. Indeed, the use of eWOM on social media has helped marketing managers to expand sales [19]. In this line, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Risk theories also shed light on consumers' search behaviors. Information is a way to reduce perceived risk [28]. Perceived risk refers to consumers' subjective expectations of loss.…”
Section: Role Of Digital Information Sources and Set Of Brand Considementioning
confidence: 99%
“…Information from actual purchasers transforms experienced goods into search goods, providing people with an "experience without ownership" [32]. Researchers also found that experts from webzines or forums influenced users' paths to purchase [28]. Experts often offer helpful information, so they are considered more reliable than other sources of information.…”
Section: Role Of Digital Information Sources and Set Of Brand Considementioning
confidence: 99%
“…The first that came into our attention is the relationship between website accessibility and e-loyalty. Scientific literature shows different insights that put accessibility into a direct or mediated relation with e-loyalty [41][42][43]. Perceived ease of use features along with perceived usefulness features and trust features regarding a website has been used to build the e-loyalty which is seen as a continued intention factor [43][44][45].…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%